A 4.92% efficiency Cu2ZnSnS4 solar cell from nanoparticle ink and molecular solution. Issue 59 (3rd June 2016) - Wang, Wei; Shen, Honglie; Wong, Lydia Helena; Su, Zhenghua; Yao, Hanyu; Li, Yufang
Abstract : Quaternary Cu2 ZnSnS4 (CZTS) thin films were prepared by a low-cost, simple and environmentally-friendly ink method. Abstract : Quaternary Cu2 ZnSnS4 (CZTS) thin films were prepared by a low-cost, simple and environmentally-friendly ink method. By depositing molecular solution on the nanoparticle thin film, the quality of as-prepared CZTS thin films was greatly improved ( e.g. reduction of fine grain layer formation and improved crystallinity). The effect of the number of spin-coated layers from molecular solution on solar cell performance was investigated. The results indicated that the CZTS thin film had the best performance when 5 layers were spin-coated from molecular solution on the nanoparticle thin film. The crystallinity of the as-prepared CZTS thin film and the interface at Mo/CZTS was found to be obviously enhanced by addition of a molecular solution layer. Finally, a CZTS thin film solar cell with an efficiency of 4.92% has been fabricated.